The Relationship Between Self-Esteem and Body Mass Index (BMI) Levels in Female High School Students at Muhammadiyah 2 Private High School in Medan - Latifah Addawiyah; Nanda Sari Nuralita; Fitri Nur Malini Siregar; Nurhasanah Nurhasanah (JURNAL IMPLEMENTA HUSADA, 2026)
Self-esteem refers to an individual's perception of how they evaluate or value themselves. This evaluation can be either positive or negative. Body Mass Index (BMI) is the ideal body weight calculated from an individual's weight and height. Weight is used as an indicator to assess nutritional status and the growth and development of children. This study is a descriptive analytic research with a cross-sectional design. The research examines the relationship between self-esteem and Body Mass Index (BMI) levels in adolescent female students by administering the Rosenberg Self-Esteem Scale (RSES) questionnaire as a measurement tool. The study sample consists of 80 participants, divided into three strata. Data analysis was performed using univariate and bivariate Chi-Square tests. The results of the test showed a significant relationship between self-esteem and Body Mass Index (BMI) levels in adolescent female students at Muhammadiyah 2 Private High School in Medan, with a significant p-value of 0.001 (p0.05). In addition, the study also assessed demographic characteristics to understand the proportion of self-esteem and BMI levels in adolescent female students at Muhammadiyah 2 Private High School in Medan. A significant relationship was found between self-esteem and Body Mass Index (BMI) levels in adolescent female students at Muhammadiyah 2 Private High School in Medan.